Harnessing natural compounds for PIM-1 kinase inhibition: A synergistic approach using virtual screening, molecular dynamics simulations, and free energy calculations: Computational screening of natural PIM-1 inhibitors - Qazi Mohammad Sajid Jamal (Cellular and Molecular Biology, 2024)
Cancer has substantial economic ramifications for healthcare systems. PIM kinases, specifically PIM-1, are commonly upregulated in different types of cancers, thereby promoting cancer development. PIM-1 inhibitors have garnered interest for their potential efficacy in cancer therapy. This study used computational methods to screen a library of 7,600 natural compounds targeting the PIM-1 active site. Five top candidates—ZINC00388658, ZINC00316459, ZINC00197401, ZINC00001673, and ZINC00316479—were selected for subsequent interaction studies, which involved molecular dynamics simulations (MDS) and free energy calculation using the MMPBSA method. These compounds interacted with key PIM-1 residues and had multiple common binding site interactions with the co-crystallized ligand 6YN, which was used as a control. Furthermore, the selected compounds exhibited favorable drug-like properties and stable docked complexes during a 200-ns molecular dynamics simulation, followed by MMPBSA analysis. Among the candidates, ZINC00388658 had the most favorable binding energy profile, indicating exceptional stability and intense interaction with PIM 1. This makes ZINC00388658 the most promising candidate for further development as a PIM-1 inhibitor. These findings suggest that ZINC00388658 and other promising compounds hold significant potential for developing new cancer therapies that target PIM-1.